Ultra relativistic electron beam spatial size estimation from angular distribution of their radiation in thin crystals - Goponov, Yu.A.; Sidnin, M.A.; Sumitani, K.; Takabayashi, Y.; Vnukov, I.E. (Вопросы атомной науки и техники, 2015)
The use of ultra relativistic electron (positron) emission in thin crystals to estimate particle beam spatial sizes for projected electron-positron colliders is proposed. The existing position-sensitive X-ray range detectors and the average path of secondary electrons in a detector restrict the minimum value of the measured beam size to a level of approximately 10 μm, which is far greater than the planned sizes of collider beams. We propose to estimate the electron (positron) beam divergence over the diffracted transition radiation from angular distribution measurements. The spatial size can be obtained from the calculated beam emittance or the experimental emittance, which is measured during the earlier stage of acceleration using optical methods. The problem of crystal destruction under the influence of a high intensity electron beam is discussed. The use of surface parametric X-ray radiation, where the problem of crystal destruction is almost absent, to measure the electron beam parameters is discussed. Пропонується використовувати випромінювання ультрарелятивістських електронів (позитронів) у тонких кристалах для оцінки розмірів пучків електрон-позитронних колайдерів, що проектуються. Існуючі позиційно-чутливі детектори рентгенівського діапазону і середній пробіг вторинних електронів у детекторі обмежують мінімальне значення вимірюваного розміру пучка величиною близько 10 мкм, що набагато більше планованих розмірів пучків колайдера. Пропонується оцінювати розбіжність пучка за кутовим розподілам дифрагованого перехідного випромінювання. Поперечні розміри можуть бути отримані з розрахованого або виміряного значень емітанса пучка, який визначається на ранніх стадіях прискорення з використанням оптичних методів. Обговорюється проблема руйнування кристала під дією електронного пучка. Пропонується для вимірювання параметрів електронних пучків використовувати поверхневе параметричне рентгенівське випромінювання, де проблема руйнування кристала повністю відсутня. Предлагается использовать излучение ультрарелятивистских электронов (позитронов) в тонких кристаллах для оценки размеров пучков проектируемых электрон-позитронных коллайдеров. Существующие позиционно-чувствительные детекторы рентгеновского диапазона и средний пробег вторичных электронов в детекторе ограничивают минимальное значение измеряемого размера пучка величиной порядка 10 мкм, что гораздо больше планируемых размеров пучков коллайдера. Предлагается оценивать расходимость пучка по угловым распределениям дифрагированного переходного излучения. Поперечные размеры могут быть получены из рассчитанного или измеренного значений эмиттанса пучка, определяемого на ранних стадиях ускорения с использованием оптических методов. Обсуждается проблема разрушения кристалла под действием электронного пучка. Предлагается для измерения параметров электронных пучков использовать поверхностное параметрическое рентгеновское излучение, где проблема разрушения кристалла полностью отсутствует.